National needs assessment of patients treated at the United States Federally‐Funded Hemophilia Treatment Centers. (30th October 2015) - Butler, R. B.; Cheadle, A.; Aschman, D. J.; Riske, B.; Senter, S.; McLaughlin, K. M.; Young, G.; Ahuja, S.; Forsberg, A. D.
Abstract : Aim: The National Hemophilia Program Coordinating Center, with the U.S. Regional Hemophilia Network conducted a national needs assessment of U.S. Hemophilia Treatment Center (HTC) patients. The objectives were to determine: (i) To what extent do patients report that they receive needed services and education; (ii) How well do the services provided meet their needs; and (iii) What are the patients' perspectives about their care. Methods: A survey was mailed to active patients of 129 HTCs. Respondents completed the anonymous surveys on line or returned them by mail. Questions focused on management and information, access and barriers to care, coping, resources, and transition. Results: Of 24 308 questionnaires mailed, 4004 (16.5%) were returned. Most respondents reported very few gaps in needed services or information and reported that services and information met their needs. Over 90% agreed or strongly agreed that care was patient‐centred and rated HTC care as important or very important. Identified gaps included dietary advice, genetic testing, information on ageing, sexual health and basic needs resources. Minority respondents reported more barriers. Conclusion: This survey is the largest assessment of the HTC population. Respondents reported that the services and information provided by the HTCs met their needs. Quality improvement opportunities include transition and services related to ageing and sexual health. Further investigation of barriers to care for minorities is underway. Results will help develop national priorities to better serve all patients in the US. HTCs.